Analisa Hasil Cetak 3D Printer Dengan Teknik Layer By Layer - I Made Ivan Wiyarta Sujana; Hendy Prasetyo (Jurnal Mekanik Terapan, 2022)
In recent years, the additive manufacturing process has developed rapidly especially in the FDM process. One of the developing FDM processes is the mixing of two filaments, namely the layer by layer technique. The technique of mixing two filaments by layer by layer is a mixing technique with the concept of layers on one specimen. The aim is to find out the strength properties of the filaments as a result of mixing layer by layer. The results of previous studies show that the mechanical properties of PLA and ABS materials are highly dependent on the level of speed and the effect of printing speed. However, to obtain the appropriate alloying results from PLA and ABS, further research is needed to adjust the parameters of the PLA and ABS alloys. so that it is expected that the layer by layer mixing technique is able to produce better mechanical properties than PLA and ABS.